2013
DOI: 10.1016/j.jbusres.2013.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership as an antecedent of change-oriented organizational citizenship behavior

Abstract: This study draws on a general framework of proactive motivation to propose and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 42 publications
7
103
1
3
Order By: Relevance
“…Therefore, empowered employees feel more competent and able to influence their outcomes (Lorinkova et al, 2013). Other studies, too, have consistently demonstrated that leaders' empowerment induces higher levels of employees' behavior and performance (e.g., Lopez-Dominguez et al, 2013;Seibert et al, 2011;Wilkins et al, 2007;Yukl, 2010). Such employee contributions satisfy specific customer demands and encourage employees to autonomously provide suggestions or services in response to varying customer demands (Liao and Chuang, 2004;Ro and Chen, 2011).…”
Section: Mediating Effect Of Psychological Contract Fulfillment Betwementioning
confidence: 98%
“…Therefore, empowered employees feel more competent and able to influence their outcomes (Lorinkova et al, 2013). Other studies, too, have consistently demonstrated that leaders' empowerment induces higher levels of employees' behavior and performance (e.g., Lopez-Dominguez et al, 2013;Seibert et al, 2011;Wilkins et al, 2007;Yukl, 2010). Such employee contributions satisfy specific customer demands and encourage employees to autonomously provide suggestions or services in response to varying customer demands (Liao and Chuang, 2004;Ro and Chen, 2011).…”
Section: Mediating Effect Of Psychological Contract Fulfillment Betwementioning
confidence: 98%
“…Leader -member exchange has similarly been found to be related to taking charge (Bettencourt 2004). More recently, López-Domínguez, Enache, Sallan and Simo (2013) found transformational leadership behaviors focused on professional development more effective in promoting changeoriented citizenship behaviors than supportive leadership behaviors. Given that the nature of the work climate can clearly shape employee proactivity (Bindl and Parker 2011), the fact that a broader range of contextual factors which are likely to impact taking charge behavior have not been studied calls for more research.…”
Section: Introductionmentioning
confidence: 98%
“…School principals' leadership style has been one of the organizational constructs potentially influencing teacher OCBs. Several studies have investigated OCBs in relation to such different leadership styles as transformational (Lian and Tui, 2012;López-Domínguez et al, 2013;Podsakoff et al, 1990;Podsakoff et al, 1996;Song et al, 2012), transactional (Lian and Tui, 2012;Nguni et al, 2006), servant (Bobbio et al, 2012), and charismatic leadership (Cavazotte et al, 2014). These studies typically adopted a principal-focused approach which regards leadership as an individual property instead of an organizational one (Hulpia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%